Smart or smash? The effect of financial sanctions on trade in goods and services - Tibor Besedeš; Stefan Goldbach; Volker Nitsch (Deutsche Bundesbank, 2022)
We examine the extent to which financial sanctions imposed by Germany through its European Union and United Nations commitments cause collateral damage on Germany's trade in goods and services. Financial sanctions reduce Germany's inflows and outflows of financial assets, as well as imports and exports of goods and services. The relative effects on trade in goods and services are weaker than on financial assets, about half as large in the case of goods and two-thirds as large in the case of services. The effect on trade in goods is entirely due to episodes where financial sanctions are accompanied by export restrictions of specific goods. In the case of services trade, only exports are affected by financial sanctions once export restrictions are considered. The primary channel through which sanctions affect the three types of cross-border flows is the extensive margin. Anticipation effects are quite strong for financial assets and weak for services and goods.
Keywords: F20; F36; F38; 330; sanction; restriction; cross-border transaction; trade in goods; trade in services financial flows